Hukum Mengucapkan Selamat Hari Raya kepada Non-Muslim Menurut Buya Yahya dan Ustadz Adi Hidayat: Penelitian - Novicha Salsabilla; Rihanatul Jannah; Adelia Septiani; Reffa Muhammad Adedyo; Alihan Satra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Safinatun Najah book has made a significant contribution in shaping the religious understanding of Muslim communities in Southeast Asia, especially in the Shafi'i school of fiqh. Buya Yahya and Ustadz Adi Hidayat provide different views on the law of celebrating holidays to non-Muslims. Buya Yahya emphasized the importance of maintaining the Islamic faith while establishing good relations. He noted that there is a difference of opinion among scholars on this matter, with a tendency to be more cautious. In contrast, Ustadz Adi Hidayat emphasized that wishing non-Muslims a happy holiday can be considered an acknowledgment of rituals that are contrary to tawhid.